2013
DOI: 10.1055/s-0033-1344614
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative elastography associated with endoscopic ultrasound for the diagnosis of chronic pancreatitis

Abstract: EUS-elastography was an accurate tool for the diagnosis of chronic pancreatitis and provided relevant and objective information to support EUS findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
89
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(95 citation statements)
references
References 22 publications
2
89
2
2
Order By: Relevance
“…Itokawa et al (27) introduced the concept of strain ratio (SR) as a semiquantitative method to objectively evaluate tissue hardness, which is simply the ratio of the distortions produced by a force on two adjacent areas. In 2013, Iglesias-García et al (23) obtained a diagnostic accuracy of 91.1% by EUSelastography using the SR for CP with a cut-off of 2.25, describing a direct correlation between the SR and the different stages of CP according to the Rosemont classification. EUS-elastography, despite obtaining a high diagnostic accuracy using indirect quantification methods, is a dependent operator technique and has a relative degree of invasiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Itokawa et al (27) introduced the concept of strain ratio (SR) as a semiquantitative method to objectively evaluate tissue hardness, which is simply the ratio of the distortions produced by a force on two adjacent areas. In 2013, Iglesias-García et al (23) obtained a diagnostic accuracy of 91.1% by EUSelastography using the SR for CP with a cut-off of 2.25, describing a direct correlation between the SR and the different stages of CP according to the Rosemont classification. EUS-elastography, despite obtaining a high diagnostic accuracy using indirect quantification methods, is a dependent operator technique and has a relative degree of invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic elastography associated with EUS is currently considered to be a complementary and useful tool in diagnosing CP, and could even classify patients according to severity (23,24). However, whether less invasive capacity techniques, such as percutaneous ARFI based elastography, could be equally relevant needs to be systematically determined.…”
Section: Introductionmentioning
confidence: 99%
“…They reported when using 4 parameters of mean, standard deviation, skewness, kurtosis, there were significant correlation between 4 parameters and grade of fibrosis evaluated pathologically (r = 0.75, 0.54, 0.69, and 0.67, respectively). Iglesias Garcia et al [63] subjected 191 chronic pancreatitis, and compared strain ratio with Rosemont classification, a well-known diagnostic criteria for chronic pancreatitis evaluated by EUS. They reported that there was positive correlation between strain ratio and Rosemont classification (r = 0.813, P < 0.0001).…”
Section: Eus-elastography -Strain Elastographymentioning
confidence: 99%
“…Investigations may include computed tomography (CT) or magnetic resonance imaging (MRI), and endoscopic ultrasound (EUS) [19].…”
Section: Introductionmentioning
confidence: 99%